DIGITAL CURRENCY VS. CRYPTOCURRENCY AND BLOCKCHAIN - Mishra Kolhe, Sarita (International Journal of Research -GRANTHAALAYAH, 2022)
Despite the Reserve Bank of India consistently raising concerns over the dangers of cryptocurrencies primarily its use is facilitating money laundering and terror financing –India has emerged as a blossoming crypto market contributing billions of dollars in trading volume. In recent years, though cryptocurrencies have gained momentum with various investors yet they have not made any significant impact due to the volatility of the transactions. The fact that cryptocurrencies require various kinds of tools like wallets, computer, internet connectivity and various other services, their usage have been restricted to only those who are technologically sound. As a result, a vast majority of the population do not have the technological know-how and hence are unable to use them. Furthermore, the complexities involved in these transactions have reduced their trust and acceptability. One of the major shortcomings is that the cryptocurrency network can only validate the payment but not the delivery of various products and services. Hence, buyer of products and services are handicapped as the network does not simultaneously validate both sides of the transactions. The sharp volatility in the value of cryptocurrencies over relatively short period of time are a major issue due to which, maintaining price stability becomes extremely difficult. Furthermore, the absence of regulatory mechanisms and decentralised nature of the transactions raises various fear and apprehension that cryptocurrencies may be used for illegal activities. The solution to get over some of the shortcomings of cryptocurrencies is the issue of digital currency by the Central Bank. The International Monetary Fund (IMF) has warned of the risks posed by cryptocurrencies especially in emerging and developing countries and has suggested coordinated action to put in place global standards for cryptocurrencies. According to the IMF, “Determining valuation is not the only challenge in the crypto ecosystem: identification, monitoring, and management of risks which defy regulators and firms are areas of concern. These include operational and financial integrity, risks from crypto assets exchanges and wallets, investor protection, inadequate reserves and inaccurate disclosure for some stable coins. According to the IMF, capital flow management may need to be fine-tuned due to digital currencies. “Crypto’s cross-sector and cross-border remit limits the effectiveness of national approaches. Countries are taking very different strategies, and existing laws and regulations may not allow for national approaches that comprehensively cover all elements of these assets. Importantly, many crypto service providers operate across borders, making the task for supervision and enforcement more difficult. Uncoordinated regulatory measures may facilitate potentially destabilizing capital flows”. In the Union Budget of 2022-23 it has been proposed that, the Reserve Bank of India would be issuing Digital Currency which would go a long way for identifying, monitoring, regulating, management of risks, and capital flow management as well as in mitigating the financial stability crisis stemming from the crypto eco-system. Furthermore, a structured taxation regime of 30 % on virtual digital assets, as well as 1 % TDS would have the potency to track investments or profits generated/ losses incurred in this type of trading of virtual digital assets. The issuance of Digital Currency by RBI as well as bringing the same within the ambit of a structured taxation regime would lead to regulation of liquidity as well as volatility and would ensure stability in the economy.